2008
DOI: 10.1590/s1517-83822008000300006
|View full text |Cite
|
Sign up to set email alerts
|

Control of brown spot pathogen of rice (Bipolaris oryzae) using some phenolic antioxidants

Abstract: Bipolaris oryzae is the causal agent of rice brown spot disease and is responsible for significant economic losses. In order to control this disease, three phenolic antioxidants were tested (salicylic acid, benzoic acid and hydroquinone). The antifungal activity of the tested substances were investigated against B. oryzae at different concentrations in vitro, as well as the efficacy of their exogenous application in controlling rice brown spot disease under field conditions. In vitro, benzoic acid or salicylic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 16 publications
6
17
0
2
Order By: Relevance
“…These results show that brown leaf spot disease of rice can effectively be controlled by various fungicides. The same has been reported by Shabana et al (2008) for fungicides and anti-oxidants against brown leaf spot. Similarly, the results of this study have also been supported by the findings of Savary et al (2000) who reported that brown leaf spot caused yield loss up to 5% along with qualitative loss and can be managed by the use of fungicides.…”
Section: Resultssupporting
confidence: 84%
“…These results show that brown leaf spot disease of rice can effectively be controlled by various fungicides. The same has been reported by Shabana et al (2008) for fungicides and anti-oxidants against brown leaf spot. Similarly, the results of this study have also been supported by the findings of Savary et al (2000) who reported that brown leaf spot caused yield loss up to 5% along with qualitative loss and can be managed by the use of fungicides.…”
Section: Resultssupporting
confidence: 84%
“…The exogenous application of phenolic compounds increases the growth of various plants such as Brassica juncea (Fariduddin et al 2003), and Cicerarietinum (Hayat et al 2012). The exogenous application of phenolic compounds is also accountable for the increase in the production of the defence enzymes and the lignin content in plants (Shabana et al 2008), since they are involved in the signal transduction as well as in the lignin synthesis pathway. The Phenolic compounds are also capable of upregulating the pathogen-related protein in wheat against Fusarium head blast (Shah and Klessig 1999).…”
Section: Cellulasementioning
confidence: 99%
“…S2; Supplemental Table S2). Benzoic acid itself exhibits antifungal activity, and pretreatment of plants with this compound increases plant resistance to fungi (Khan et al, 2001;Williams et al, 2003;Shabana et al, 2008). Similarly, benzoic acid levels increase in response to both bacterial and viral infection (Shapiro and Gutsche, 2003;Matsuura et al, 2009).…”
Section: Carboxylic Acidsmentioning
confidence: 99%